Універсальна методика розрахунку обмоткових коефіцієнтів - Лущик, В'ячеслав Данилович (НТУ "ХПІ", 2011)
Описана універсальна методика розрахунку обмоткових коефіцієнтів, яка основується на використанні комплексних чисел. Методика надзвичайно проста і дозволяє обчислювати обмоткові коефіцієнти будь-яких обмоток без винятку. Рзглянуті деякі публікації останніх років, які присвячені розрахункам обмоткових коефіцієнтів

The universal method of winding coefficients calculation is expounded, which is based on the use of imaginaries. A method is extraordinarily simple and allows to calculate the winding coefficients of any winding without an exception. Some publications of the last years which are devoted the calculations of winding coefficients are considered
Universal method of winding coefficients calculation
Keywords: енергія; магнітне поле; полюс; фаза; winding coefficients; calculations method